2015
DOI: 10.1002/2015jd023584
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the predictability and physical mechanisms of an extreme-rainfall-producing mesoscale convective system along the Meiyu front in East China: An ensemble approach

Abstract: Forecast uncertainties and physical mechanisms of a quasi-linear extreme-rain-producing mesoscale convective system (MCS) along the Meiyu front in East China, during the midnight-to-morning hours on 8 July 2007, are studied using ensembles of 24 h convection-permitting simulations with a nested grid spacing of 1.11 km. The simulations reveal a strong sensitivity to uncertainties in the initial state despite the synoptic environment being favorable for heavy rainfall production. Linear changes of a less skillfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 70 publications
(120 reference statements)
1
59
0
Order By: Relevance
“…Journal of Geophysical Research: Atmospheres 10.1002/2016JD025913 covers the Yangtze River basin and the Jiang-Huai region, supplying abundant water vapor favorable for the occurrence of precipitation. Jiang-Huai region is dominated by Meiyu rain belt during the summer season [Ding et al, 2008;Luo and Chen, 2015]. An enhanced WNPSH transports more water vapor to the southern flank of Jiang-Huai region.…”
Section: Water Vapor Transport Background Of the East Asia Summer Monmentioning
confidence: 99%
“…Journal of Geophysical Research: Atmospheres 10.1002/2016JD025913 covers the Yangtze River basin and the Jiang-Huai region, supplying abundant water vapor favorable for the occurrence of precipitation. Jiang-Huai region is dominated by Meiyu rain belt during the summer season [Ding et al, 2008;Luo and Chen, 2015]. An enhanced WNPSH transports more water vapor to the southern flank of Jiang-Huai region.…”
Section: Water Vapor Transport Background Of the East Asia Summer Monmentioning
confidence: 99%
“…The MCS producing the heavy rainfall of case 3 initiated and developed locally in central Guangdong (Figure c). At its mature stage it consisted of several well‐defined, southwest‐northeast oriented band‐shaped convective precipitation regions with reflectivity >35 dB Z (simply referred to herein as rainbands) during its mature stage (Figures c3 and c4), exhibiting “band training” [ Luo et al ., ; Luo and Chen , ] of the rainbands along the MCS. The rainbands appeared quasi‐stationary, continuously producing rain over the same areas for nearly 20 h (i.e., 1630–1230 UTC, Figures c2–c5).…”
Section: Forecast Evaluation For Four Torrential Rainfall Casesmentioning
confidence: 99%
“…The impact of differences in the initial moisture field on predictions of an extreme rain‐producing MCS, ahead of a Meiyu front in central East China, has been investigated by Luo and Chen [] using ensemble simulations with the WRF model [ Skamarock et al ., ], following the method proposed by Melhauser and Zhang []. Luo and Chen [] found that reducing the initial precipitable water in the upstream region by only a few millimeters could cause the maximum 14 h accumulated precipitation in the simulations to change from 85 mm to 259 mm. For the cases of interest to the present study, the water vapor is transported by the low‐level southwesterly flow in the ensembles (Figure ).…”
Section: Key Synoptic Factorsmentioning
confidence: 99%
“…Houtekamer et al () introduced the multiphysics approach in which each ensemble member uses a distinct parametrization of the same physical process. Multiphysics have been shown to improve ensemble forecast skill on the convection‐parametrizing (Berner et al , ; ) and on the convection‐permitting scale (Clark et al ; Luo and Chen, ). In the multiparameter approach (Murphy et al ), single parameters in the physics parametrizations are varied within their range of allowed values or perturbed randomly about their default value.…”
Section: Introductionmentioning
confidence: 99%